Sistemas de equações lineares: - PINHEIRO, Ana Luiza Rosa (Universidade Federal do Tocantins, 2023)
This work consists of a study of Systems of Linear Equations. For this, we present the theory of Matrices and Determinants, since they are prerequisites for their understanding. A system of li- near equations is a set of equations of degree one. When studying linear systems, the main goal is to find your solution set, which often depending on the number of equations and unknowns, this does not become so simple. We will bring in this work the main methods of solving sys- tems and also the necessary conditions for their use. At the end of the study, we will present two didactic proposals for the teaching of systems of linear equations in secondary education, since the National Curricular Parameters - PCN’s provide the necessary basics, in which we must both seek to relate mathematical to everyday life, As this brings a practical meaning of this content to the student as well as addressing new content through problem solving from the traditional method and trying to innovate with a contextualized lesson of solving exercises. The methodo-logy used involves a bibliographical research, through readings in articles, monographs, course papers, dissertations, Linear Algebra books and Algebra with Applications.